HISTORICAL ANALYSIS OF EDUCATIONAL PROCESS SYSTEM IN MOVAROUNNAHR - Imamov Ulug’bek Ismailovich (Scholars Digest Publishing, 2023)
Humanity recognized itself, tried to know life, nature, teach young people to live, and solve the problems of the time on the basis of deep worldview, life experience and social needs: they created various writings, and there were teachers (teachers) and students (students) of them. There is little information about the educational system and institutions of the ancient period, because due to various events of the recent history, we have not preserved the sources that reveal this. Since most of the information in the sources that have been preserved to us belong to the periods when Islamic civilization spread in our country, the educational system and institutions are mentioned in the Arabic terms, i.e. school, madrasah (ibtidoiya), madrasah (aliya). During the lesson, the teacher read the book to the students, which was difficult to master at first. The material read was written down by the student on the board in the necessary cases. As a result, the material was read aloud by the student, and the teacher corrected the mistakes and commented on some necessary situations. The main emphasis here is on the student's memory.
Keywords: Maarif, primary, general and higher education, madrasahs, teacher, student, khalfa, kataba, sheikh, dargah, dictionary analysis, architectural harmony, painting, evenness, tiling, abjad method, arabic writing.